De-pathologizing perversion: Proust's sexual discourses and their Chinese translations. Issue 1 (2nd January 2020) - Li, Shuangyi
ABSTRACT: The sexological aspects of Proust's work have largely been neglected in its Chinese reception. This article focuses on Chinese (re)translations of Proust's sexual discourses in À la recherche du temps perdu and expounds the epistemic challenges of and the evolving strategies for translating sadomasochism and homosexuality into Chinese. It further explores how these observations refract the changing and largely de-pathologizing discourses on, and social attitudes to, sadomasochism and homosexuality in China from the late 1980s until now. A close examination of exemplary passages (from Du côté de chez Swann, Sodome et Gomorrhe, La Prisonnière, and Le Temps retrouvé ) in different Chinese translations reveals a lexical and conceptual appropriation and recontextualization of modern Western as well as traditional Chinese discourses on/of sexology.